Choledocholithiases in a child with Hemoglobin Evans [alpha2 62(E11) Val→Met]. Issue 7 (1st June 2016) - Hayakawa, Itaru; Hataya, Hiroshi; Kaneko, Takashi
Key Clinical Message: We present the first description of choledocholithiases in a 10‐year‐old boy with Hemoglobin Evans. Although biliary stones are much less common in children than in adults, epigastric pain in children with known hemolytic status should alert the physician to the possibility of biliary colic. Abstract : We present the first description of choledocholithiases in a 10‐year‐old boy with Hemoglobin Evans. Although biliary stones are much less common in children than in adults, epigastric pain in children with known hemolytic status should alert the physician to the possibility of biliary colic.